A critical review of literature on English language teaching textbook evaluation: What systemic functional linguistics can offer - Zhang Xiaodong (Journal of Language and Cultural Education, 2017)
This paper, from the perspective of language learning as a meaning-making process, presents a critical review of the existing research on how pre-use, in-use, and post-use evaluation has investigated the relationship between English language teaching textbooks’ content and learners’ academic literacy development. The paper shows that previous research on these three types of evaluation examined English language teaching textbooks’ effect on English learners’ academic literacy development in an unprincipled and macro way. The research gap identified in these previous studies calls for an improved textbook evaluation framework that integrates a principled learning theory while simultaneously emphasizing macro-constructs (e.g., context) and micro-linguistic features needed for academic literacy development. To this end, this paper proposes a framework informed by Systemic Functional Linguistics-related constructs (e.g., genre, register, meta-meanings, and lexico-grammar system) to optimize the evaluation of English language teaching textbook content.